Experimental Study on the Sound Absorption Properties of Finger Millet Straw, Darbha, and Ripe Bulrush Fibers. (28th December 2021) - Rakesh, K. M.; Srinidhi, Ramachandracharya; Gokulkumar, S.; Nithin, K. S.; Madhavarao, S.; Sathish, S.; Karthick, Alagar; Muhibbullah, M.; Osman, Sameh M.
Abstract : Nowadays, emerging noise pollution by external factors causes harmful diseases in human beings. The development of a bio-based filler or panel will help to eliminate some unwanted noise in working places and living rooms. This work aimed to develop an ecowaste fiber (leftover after harvesting)-based sound absorber and analyze its capabilities for sound absorption. The ecowaste fibers are collected by the gleaning process, i.e., the process of collecting leftovers from fields. The sound absorption capabilities of three natural fibers extracted from Eleusine coracana (Finger millet) straw, Desmostachya bipinnata (Darbha), and Typha domingensis (Ripe bulrush) plants are investigated in this study, both individually and in hybrid combinations. The sound absorption property mainly depends on factors such as porosity, flow resistivity, thickness, density, and tortuosity. Fiber length and fiber type play a significant role when fibers are arranged individually or in hybrid combinations. The stacking effect on the sound absorption coefficient of hybridized fiber arrangement was experimentally analyzed. The sound absorption coefficient ( α ) was found to be lower in the range of 1000 Hz–2500 Hz for all the combinations. As a homogenous fiber arrangement, the darbha fiber exhibited the better NRC (noise reduction coefficient) of 0.86 for 50 mm thickness among three different fibers and as a hybrid composition, ripe bulrush and darbha fibers exhibited NRC of 0.90 which is more capable of absorbing sound in the critical frequency range of 500 to 2000 Hz. These types of natural fiber fillers are highly capable of better sound absorbing and used in the applications such as classrooms, sound recording rooms, and theatres.